2021
DOI: 10.3389/fimmu.2021.725223
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Hypoxia Risk Score Predicts the Clinical Outcomes and Tumor Microenvironment Immune Characters in Bladder Cancer

Abstract: BackgroundBladder cancer (BLCA) is one of the most common urinary malignancies with poor prognosis. There is an unmet need to develop novel robust tools to predict prognosis and treatment efficacy for BLCA.MethodsThe hypoxia-related genes were collected from the Molecular Signatures Database. The TCGA-BLCA cohort was downloaded from the Cancer Genome Atlas and then was randomly divided into training and internal validation sets. Two external validation cohorts were gathered from Gene Expression Omnibus. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Despite the prominent role of TGF-b in regulating multiple cancer processes, therapies targeting the TGF-b pathway have not been well explored (10). With the improvement of genomic sequencing methods, more and more genomic signatures have been created to predict the prognosis and therapeutic opportunities for cancers (8,23,24). In BLCA, Stojnev et al explored the roles of three key components (TGF-b1, Smad2, and Smad4) of the canonical TGFb pathway in predicting the prognosis (25).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the prominent role of TGF-b in regulating multiple cancer processes, therapies targeting the TGF-b pathway have not been well explored (10). With the improvement of genomic sequencing methods, more and more genomic signatures have been created to predict the prognosis and therapeutic opportunities for cancers (8,23,24). In BLCA, Stojnev et al explored the roles of three key components (TGF-b1, Smad2, and Smad4) of the canonical TGFb pathway in predicting the prognosis (25).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hypoxia as a factor that alters the tumor characteristic microenvironment can accelerate tumor metastasis and enhance drug resistance ( Zandberg et al, 2021 ). Numerous studies have confirmed that there is a hypoxic microenvironment in most solid tumors, including BCa, and the expression of hypoxia-related genes will affect the TME, the efficacy of therapeutic drugs, and patient prognosis ( Yang et al, 2017 ; Liu et al, 2021 ). However, some previous studies have verified that some HRLs will also affect tumor progression, and the HRL risk model can also predict the patient prognosis well and has an effect on clinical therapy ( Shao et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of gene-sequencing technology, many hypoxia-related signatures have been established in multiple tumors to predict patient prognosis and treatment efficacy, such as immunotherapy and chemotherapy response ( Shao et al, 2021 ; Sun et al, 2021a ). In BCa, multiple hypoxia-related gene signatures were developed and validated to predict prognosis and TME immune characteristics ( Yang et al, 2017 ; Liu et al, 2021 ). In recent years, with the successful application of immunotherapy in tumors, an increasing number of people have begun to pay attention to the clinical value of immune checkpoints, such as anti-PD-L1/PD-1 therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations